THE CONDOLENCE BETWEEN ARAB AND PERSIAN - Majid Merhij (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Condolence at both, the Iraqi and Persian environment is an ancient as the ancient history of these two Nations. The Arabic Literature had the priority in Condolences establishment, then it transferred to the Literary Persian Environment (Iran) as a soft environment to receive such phenomenon. The condolence may different in its Art prospects and phenomena between the two adjacent Nations, and the influence on each other is something normal due to Arab and Persian Nations differences in most of the popular components, religion believes and Ethnic origins.